Multinomial Selection in the Presence of Infinite Alternatives. Issue 5 (27th May 2016) - Vieira Junior, Hélcio; Kienitz, Karl Heinz; Belder-Rain, Mischel Carmen Neyra
Abstract : We propose a new procedure for the multinomial selection problem to solve a real problem of any modern Air Force: the elaboration of better air-to-air tactics for Beyond Visual Range air-to-air combat that maximize its aircraft survival probability H (θ, ω), as well as enemy aircraft downing probability G (θ, ω). In this study, using a low-resolution simulator with generic parameters for the aircraft and missiles, we could increase an average success rate of 16.69% and 16.23% for H (θ, ω) and G (θ, ω), respectively, to an average success rate of 76.85% and 79.30%. We can assure with low probability of being wrong that the selected tactic has greater probability of yielding greater success rates in both H (θ, ω) and G (θ, ω) than any simulated tactic.